Alpha-Synuclein Post-translational Modifications: Implications for Pathogenesis of Lewy Body Disorders - Manzanza, Nelson de Oliveira; Sedlackova, Lucia; Kalaria, Raj N. (Frontiers in Aging Neuroscience, 2021)
Lewy Body Disorders (LBDs) lie within the spectrum of age related neurodegenerative diseases. They are considered to be among the second most common form of neurodegenerative dementia after Alzheimer’s disease. They are progressive conditions with variable clinical symptoms embodied within specific cognitive and behavioural disorder. There are no currently effective treatments for LBDs. LBDs are histopathologically characterized by the presence of abnormal neuronal inclusions called Lewy Bodies (LB) and extracellular Lewy Neurites (LN). and LBs and LNs are predominantly composed of alpha-synuclein (aSyn) aggregates. It has been proposed that posttranslational modifications such as aSyn phosphorylation, ubiquitination SUMOylation, Nitration, o-GlcNacylation and Truncation play important roles in the formation of toxic forms of the protein, which consequently facilitates the formation of these inclusions. This review focuses on the involvement of different posttranslational modifications (PTMs) of aSyn described in the spectrum of the synucleinopathies, with a particular focus on LBD. We highlight how these PTMs interact with aSyn to promote misfolding and aggregation and interplay with membranes leading to the potential functional and pathogenic consequences detected so far, and their particular involvement in the development of LBD.